2019
DOI: 10.1186/s12943-019-0988-0
|View full text |Cite
|
Sign up to set email alerts
|

MCT-1/miR-34a/IL-6/IL-6R signaling axis promotes EMT progression, cancer stemness and M2 macrophage polarization in triple-negative breast cancer

Abstract: BackgroundTriple-negative breast cancer (TNBC) is a poor prognostic breast cancer with the highest mutations and limited therapeutic choices. Cytokine networking between cancer cells and the tumor microenvironment (TME) maintains the self-renewing subpopulation of breast cancer stem cells (BCSCs) that mediate tumor heterogeneity, resistance and recurrence. Immunotherapy of those factors combined with targeted therapy or chemoagents may advantage TNBC treatment.ResultsWe found that the oncogene Multiple Copies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
274
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(286 citation statements)
references
References 53 publications
12
274
0
Order By: Relevance
“…The IL‐6/Stat3 pathway was identified to cross‐talk with CD155 in TNBC cells. IL‐6 was involved in TNBC cell growth, survival, migration, metastasis and stemness . As a downstream intracellular molecule of IL‐6, Stat3 was also overactivated in TNBC, and associated with the aggressive phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…The IL‐6/Stat3 pathway was identified to cross‐talk with CD155 in TNBC cells. IL‐6 was involved in TNBC cell growth, survival, migration, metastasis and stemness . As a downstream intracellular molecule of IL‐6, Stat3 was also overactivated in TNBC, and associated with the aggressive phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…Then, the STAT 3 complex is transferred from the cytoplasm to the nucleus, binds to a consistent DNA element, and initiates transcription of STAT 3 target genes, including cyclinD 1, Bcl‐XL, c‐myc, MCL 1, and VEGF . Additionally, IL‐6 is modulated by multiple miRNAs, for instance, miR‐34a negatively modulates IL‐6 in breast cancer to exert a tumor suppressor effect . miR‐608 binds to the 3′UTR of IL‐6 to inhibit ESCC progression .…”
Section: Discussionmentioning
confidence: 99%
“…22,24 Additionally, IL-6 is modulated by multiple miRNAs, for instance, miR-34a negatively modulates IL-6 in breast cancer to exert a tumor suppressor effect. 43 miR-608 binds to the 3 0 UTR of IL-6 to inhibit ESCC progression. 42 We demonstrated that circ_0000654 enhanced IL-6/STAT3 expression in ESCC cells, and activation of IL-6/STAT3 in ESCC cells partially reversed the effect of circ_0000654 or attenuated the tumorsuppressive function of miR-149-5p.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulating evidence suggests that the density of stroma‐infiltrating immune cells reflects the focal immune response of patients to chemotherapy regimens and may serve as a promising predictor 11‐13 . Although some studies have investigated the prognostic relevance of some immune cells in TNBC, there are few systematic studies on the association between the overall stromal immune cell signature and clinical outcomes 12,14,15 …”
Section: Introductionmentioning
confidence: 99%